(untitled) (Research, Society and Development, 2020)
Sugarcane (Saccharum officinarum L.) is a product grown in different regions of Brazil and has great importance for the country’s economy, being used in the production of sugar and alcohol. As a final result of the production of the sugar and alcohol sector, sugarcane bagasse has been studied as an alternative application in different areas, among them, in food science. Thus, the study aimed to analyze the quality parameters of the sugarcane bagasse flour. The samples were subjected to drying in an air circulation oven at different temperatures (50ºC, 55ºC and 60ºC). With the flours obtained by drying the bagasse, the physical-chemical and chemical composition parameters were determined (AOAC, 2005). The dehydrated flour at a temperature of 55ºC demonstrated better stability in terms of loss of mass during drying. Flours showed higher yield in the granulometry of the base (<0.425mm), regardless of drying temperatures. In the parameters of proximate composition, the flours showed moisture (3.96% to 5.35%), proteins (0.93% to 1.55%), lipids (0.16% to 0.65%), carbohydrates (92.30% to 93.61%) and energy value (376.86% to 384.08%). In the process of dehydrating sugarcane bagasse, regardless of temperature, the drying time influenced the loss of mass, stabilizing after 75 minutes of drying. All flours have physico-chemical characteristics that allow good storage stability, mainly due to the low water activity.